Caregiver Expressed Emotion in Families of Youth With Spina Bifida: Demographic, Medical, and Family Correlates. (26th September 2022) - Stiles-Shields, Colleen; Kritikos, Tessa K; Winning, Adrien M; Starnes, Meredith; Holmbeck, Grayson N
Abstract: Objective: Caregiver expressed emotion (EE), an interview-based measure of emotional valence within an interpersonal relationship, is associated with psychosocial outcomes across multiple conditions. Guided by a model implicating a bidirectional role of "Chronic Family Stress" in the unfolding of EE in family environments, the current study examined demographic, medical, and family-level variables in association with EE in caregivers of children with spina bifida (SB). Methods: Data were combined from 2 distinct studies of families with a child with SB, resulting in a sample of 174 (ages 8–17). Linear regressions examined the family stressors and child variables in association with maternal and paternal warmth and criticism, as coded from EE interviews. Results: Higher levels of family stress were associated with paternal criticism ( p = .03), while having non-Hispanic White children was associated with both maternal and paternal criticism ( p s < .005). Having children younger in age ( p s < .01) and without a shunt ( p s < .01) was associated with higher warmth. Conclusions: Family stressors, absence of the negative impacts of systemic racism, shunt status, and age appear to be associated with the expression of EE in caregivers of a child with SB. Findings highlight multiple assessment considerations, including assessing EE when children are younger to engage caregivers with children with SB when they are more likely to be expressing more warmth. Pinpointing factors associated with caregiver EE in SB will help to better identify families at risk for high levels of criticism and also aid in the development of targeted prevention and intervention programs.